Chapter 9 CHERISH Development of a Toolkit for the 3D Documentation and Analysis of the Marine and Coastal Historic Environment - Corns, Anthony (Taylor & Francis, 2024)
Ireland and Wales have a combined coastline of approximately 9,000 km in length, comprised of a combination of rock and soft sediment. Many archaeological and historical sites along this coastline are at risk of being damaged or destroyed by the present and future effects of climate change. The EU funded CHERISH Project (Climate, Heritage and Environments of Reefs, Islands, and Headlands) of the Irish and Welsh regional seas is researching these threats. This chapter focuses on those methods and applications within the CHERISH toolkit and explores the different ways 3D data collected within a project is being used to derive seamless terrain datasets to close the data deficit ("white ribbon") which currently exists between the terrain and marine environments. These methods are currently being developed and employed to record, map, analyse and interpret the 3-dimensional nature of both the coastal and marine historic environments.